Reflecting on the powers, possibilities and constraints of geography curricula in England, Finland and Sweden - Hammond, L; Healy, G; Bladh, G; Tani, S (Taylor and Francis, 2024)
National curriculum statements found within the Official Recontextualising Field (ORF) provide an insight into how geography as a school subject is conceptualised in a country’s education system. National curricula can shape teachers’ agency in curriculum making and what, how and where children and young people study and learn geography. This paper engages with the lower secondary national geography curriculum for England, Finland, and Sweden. We examine the structure and nature of the national geography curricula in each country, before drawing on Lambert et al.’s (2015) threefold arrangement of geographical knowledge as a tool for analysis of the curricula. Our analysis found that deep and descriptive world knowledge forms the largest proportion of all three national curricula documents, and we argue that this can lead to a potentially limited conceptualisation of geographical knowledge and representation of geography. We also suggest that the threefold arrangement could more actively engage with political dimensions when considering futures, and that there should be greater attention paid to the histories and geographies of the discipline (geography) in school geography.